1997
DOI: 10.1136/jnnp.63.2.228
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic effects of selegiline: possible cardiovascular toxicity in Parkinson's disease

Abstract: Objectives-The United Kingdom Parkinson's Disease Research Group (UKP-DRG) trial found an increased mortality in patients with Parkinson's disease randomised to receive selegiline (10 mg/day) and levodopa compared with those taking levodopa alone. Unwanted eVects of selegiline on cardiovascular regulation have been investigated as a potential cause for the unexpected mortality finding of the UKPDRG trial. Methods-The cardiovascular responses to a range of physiological stimuli, including standing and head up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
47
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(53 citation statements)
references
References 39 publications
5
47
0
1
Order By: Relevance
“…Blood pressure (BP) and heart rate (HR) were measured when supine for 20 minutes, during head-up tilt to 45°at 2 and 10 minutes, and on standing at 2 minutes as previously described. 3,5 Cardiovascular responses to other physiological challenges were not examined because no patient had autonomic failure. Patients were continuously monitored with a three-lead electrocardiogram.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Blood pressure (BP) and heart rate (HR) were measured when supine for 20 minutes, during head-up tilt to 45°at 2 and 10 minutes, and on standing at 2 minutes as previously described. 3,5 Cardiovascular responses to other physiological challenges were not examined because no patient had autonomic failure. Patients were continuously monitored with a three-lead electrocardiogram.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous series of Parkinson's disease (PD) patients without underlying autonomic failure, we found that selegiline in combination with L-dopa caused selective and predominantly systolic orthostatic hypotension which was abolished by withdrawal of the drug. 3 The mechanism(s) by which selegiline might cause orthostatic hypotension is unknown. Although not formally examined because of the study design, motor function deteriorated within a week of stopping selegiline in most patients in our first study.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6,13 In addition, a potential disadvantage of selegiline is its metabolism to (-)-amphetamine and (-)-methamphetamine, which may be related to its adverse effects. 14,15 In contrast, rasagiline has no amphetamine metabolites, 7 and its major metabolite, 1(R)-aminoindan, is devoid of amphetamine-like properties or other toxicity.…”
mentioning
confidence: 89%
“…These studies noted that patients taking selegiline long term had a higher risk of orthostatic hypotension [36][37][38][39]. However, no studies have yet shown a causal relationship between selegiline and cardiotoxicity that may explain the increased death rate.…”
Section: Figurementioning
confidence: 99%